Efektivitas Penggunaan Alat Permainan Edukatif Balok dalam Mengembangkan Kemampuan Kognitif Anak di TK PGRI - riana rahayu (Bahasa Indonesia, 2026)
ABSTRACT Cognitive development is an essential aspect of early childhood growth, as it encompasses children's ability to think, reason, solve problems, and understand their surrounding environment. The development of cognitive abilities is influenced by both innate potential and environmental stimulation, including educational experiences provided through play-based learning activities. Educational game tools serve as instructional media that facilitate meaningful learning experiences and support various aspects of child development. This study aims to examine the effectiveness of educational block games in enhancing the cognitive abilities of early childhood learners. The research employed a qualitative approach, with data collected through interviews conducted with a teacher at TK PGRI Sukarame. The findings indicate that the use of educational block games positively contributes to the development of children’s cognitive skills. Through block play activities, children gradually improve their ability to recognize and differentiate shapes, colors, sizes, and spatial relationships while also strengthening problem-solving and critical thinking skills. Furthermore, the integration of varied and engaging learning activities helps maintain children's interest and motivation throughout the learning process. The study concludes that educational block games represent an effective learning medium for stimulating cognitive development and fostering active learning among early childhood learners. Keywords: Educational Game Tools, Block Games, Cognitive Development, Early Childhood Education, Learning Media.